Eksistensi Perempuan dalam Novel Rembang Jingga Karya Tj Oetoro Dan Dwiyana Premadi: Kajian Feminisme Eksistensialis Simone De Beauvoir - Nursih Fauziah; Nurizzati Nurizzati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Women become one of the phenomena that often exist in the novel. Women are depicted as weak parties so that they are often used as an excuse for men to exploit their beauty. Over time the existence of women is increasingly visible in terms of fighting for rights and equalizing their position with men. This study aims to explain the forms and strategies in the existence of women in the novel Rembang Jingga by Tj Oetoro and Dwiyana Premadi. This study uses a type of literary research with a descriptive method. The data collection technique used was reading the novel as a whole, marking the parts indicated on the existence of women and taking an inventory of the data. The data analysis technique is to describe the data, classify and interpret the data. The research findings include 1) the forms of women's existence in the novel Rembang Jingga there are two kinds, namely first, there are for themselves in the form of unyielding, strong women and the will to fight, second, there are for others. 2) There are four strategies for the existence of women in the Rembang Jingga novel, namely working women, intellectual women, social transformation women, and independent women